Improving software requirements reasoning by novices: a story‐based approach. Issue 6 (1st December 2019) - Fatima, Rubia; Yasin, Affan; Liu, Lin; Wang, Jianmin; Afzal, Wasif; Yasin, Atif
Abstract : Requirements elicitation is one of the essential steps towards software design and construction. Business analysts and stakeholders often face challenges in gathering or conveying key software requirements. There are many methods and tools designed by researchers and practitioners but with the persistent development of new technologies, there is a need to make requirements gathering and design‐rationale process more efficient and adaptable. Storytelling is an emerging concept and researchers are witnessing its effectiveness in education, community building, information system, and requirement elicitation. Objectives of this study are to devise a method for requirements elicitation and improving design‐rationales using story‐based techniques and evaluate the effectiveness of the proposed activity. To answer the research objectives, the authors have conducted open‐ended interviews to get feedback on the proposed method; the authors have case requirement from a running project to map how this method can be useful; and performed empirical evaluation of the proposed card‐based activity. The estimated regression model, in our study, has shown that participants' perception about the simplicity/easiness and the joy of playing the game has an eventual positive effect on requirements elicitation through enhancing user's desire to play the game, which in turn increases the collaborative learning outcomes of the game.